Quality management of the education in higher education institutions of Ukraine on the principles of business socially responsibility - Oksana , Polinkevych; Nataliia , Pavlikha; Maksym, Voichuk (National Interest, 2022)
The article systematizes the elements that determine the quality of higher education according to ISO, EFQM, MBNQA, SQAF, ABEF, TQM. The main approaches to the formation of quality education in Ukraine are outlined. Peculiarities of providing quality education in Ukraine are determined. It is noted that the quality of education affects the country's competitiveness and its place in world rankings.